Progam Ekstrakulikuler Drumband dalam Menunjang Kemampuan Seni Musik Siswa Sekolah Dasar - Ula Aulia As Sanusi; Wasis Wijayanto (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
This study looks at how the drum band at SDN 1 Kedungwaru Kidul supports the musical arts abilities of elementary school pupils as an extracurricular activity. It is anticipated that children's IQ would increase as they learn music. The growth of other intelligences is greatly aided by this intellect. Participating in extracurricular drumband training is one way to enhance musical arts abilities. participants in elementary school. On October 4, 2025, 24 grade VI students who had been actively involved in drumband activities for about a semester engaged in music art classes and conducted supervisor interviews in order to collect data. This study employs a qualitative methodology using a case study format to analyze data gathered by observation, documentation, and interviewing techniques. In research, data triangulation is used to verify the accuracy of the data. The study's findings demonstrate that the Drumband Extracurricular Program's implementation process has been proceeding smoothly. Damaged equipment, a shortage of practice time, and pupils who are not focused and diligent in performing the exercises are the challenges encountered. Increasing practice time, purchasing new equipment or repairing broken equipment, and providing constant guidance and direction are the strategies to get beyond these challenges and ensure that drum band practice runs well. The study's recommendations include the necessity of additional research to look at the factors that make drum band extracurricular activities successful and the execution of other arts extracurricular programs at the primary school level